Peran Anggaran Informasi Akuntansi Terhadap Pusat Pertanggungjawaban Biaya - Lesi Hertati (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2021)
Responsibility arises because of the delegation of authority from a higher level of management to a lower level. To know responsibilities, lower management must know clearly what authority should be delegated by their superiors. Lower management should be responsible for the execution of the authority assigned to it. Therefore, the need arises for the organization that is authorized for accounting accounting to assess the accountability of the exercise of authority. Validity tests were carried out which were used to determine the items in the list of questions to determine the variables being tested. The variant known as SEM PLS to test the hypothesis is carried out to test exogenous variables against endogenous variables directly, namely by comparing t-tables and t-counts. Each result of this calculation is then compared with the t-table obtained using an error level of 0.05. The target population of this study is the district/city SKPD in South Sumatra. The data collection that became the primary data source was the method of collecting data which was carried out by the author himself directly to the object of research. The method is obtained by: (a) Interview (Interview) and (b) Observation (Observation). Then secondary data is data collection in the form of publication results or data that has been collected by other parties or agencies. The method obtained by collecting data where the data related to the object of research obtained. This study is to determine the role of the budget, accounting information on the responsibility center. The results of the study prove that the budget responsibility center can be used to monitor, analyze, implement, control and make decisions. The data collection method uses the Structural Equation Model (SEM) with the Partial Least Square (PLS) method.